The Impact of Google Translate on High School Students’ Writing Ability - Perdana, Malik Fajar Anjang; Arifani, Yudhi (Jetlal, 2024)
The rapid development of information and communication technology, Google Translate has become a tool that used often in education, especially to help student in written assignments. This study aims to explore the impact of using Google Translate on high school students' writing abilities. This research uses mixed methods including, quantitative methods with a quasi-experimental design and using a questionnaire to measure students' perceptions on how much impact Google Translate has on writing skills. Quantitative methods with the Independent Samples T-test to assess differences in writing ability between groups who use Google Translate and those who do not. In addition, descriptive analysis was carried out on questionnaire data to understand students' perceptions of the impact of Google Translate in the writing learning process. The results show that the use of Google Translate has a positive impact on increasing students' writing scores. However, there is variation in student perceptions regarding the effectiveness and accuracy of these tools. This research provides important insights for educators in integrating technology in education, by considering the benefits and limitations of these digital translation tool in the context of learning to write.